Recent progress in the roles of microRNAs in pulmonary arterial hypertension associated with congenital heart disease - Siregar, Fajri M.; Hartopo, Anggoro B.; Mubarika, Sofia (Narra Sains Indonesia, 2024)
Research on noncoding RNA, particularly microRNAs (miRNAs), is growing rapidly. Advances in genomic technologies have revealed the complex roles of miRNAs in pulmonary arterial hypertension (PAH) associated with congenital heart disease (CHD). It has been demonstrated that the progression of PAH associated with CHD is characterized by particular dysregulation of miRNAs and is related to cardiovascular remodeling, cell death, and right ventricle dysfunction. This review provides a comprehensive overview of the current state of knowledge regarding the involvement of miRNAs in the pathogenesis and progression of PAH associated with CHD. We commence by explaining the process of miRNA synthesis and its mode of action, as well as the role of miRNA in PAH associated with CHD. Moreover, the article delves into current breakthroughs in research, potential clinical implications, and prospects for future investigations. The review provides the insight into novel approaches for diagnosis, prognosis, and therapy of PAH associated with CHD.